Worries and Concerns among Inflammatory Bowel Disease Patients Followed Prospectively over One Year - Lars-Petter Jelsness-Jørgensen; Bjørn Moum; Tomm Bernklev (Gastroenterology Research and Practice)
Disease-related worries are frequently reported in inflammatory bowel disease (IBD), but longitudinal assessments of these worries are scarce. In the present study, patients completed the rating form of IBD patient concerns (RFIPC) at three occasions during one year. One-way analysis of variance (ANO VA), t-tests, bivariate correlation, and linear regression analyses were used to analyse data. The validity and reliability of the Norwegian RFIPC was tested. A total of 140 patients were included (V1), ulcerative colitis (UC) n = 92, Crohn's disease (CD) n = 48, mean age 46.9 and 40.0-year old, respectively. The highest rated worries included having an ostomy bag, loss of bowel control, and reduced energy levels. Symptoms were positively associated with more worries. A pattern of IBD-related worries was consistent over a period of one year. Worries about undergoing surgery or having an ostomy bag seemed to persist even when symptoms improved. The Norwegian RFIPC is valid and reliable.